(untitled) (Journal of Comparative & International Higher Education, 2024)
In response to calls for more individualized research on international student mobility (ISM), this article reports on a hermeneutic phenomenological study into the lived experience of two participants, one from Inner Mongolia and one from Ecuador, who migrated internationally for higher education. Within a constructivist epistemological framework, this study reveals how these participants describe and interpret their international mobility experience across four semi-structured interviews over a ten-year period. Four key themes were identified through interpretive data analysis: (1) study abroad as self-initiated and self-fulfilling; (2) key moments shaping the experience (10-year lens); (3) self-actualization via international student mobility; and (4) complex perceptions relating to “home.” A key contribution of this research is substantiating how individuals display agency within the context of ISM, both in their practical responses to circumstances and in their growing sense of self-actualization.